From waves in complex systems to dynamics of generalized continua : tributes to Professor Yih-Hsing Pao on his 80th birthday - Hutter, Kolumban; Wu, Tsung-Tsong, 1955-; Shu, Yi-chung, 1968- (World Scientific Pub., 2011)
The book reviews recent research activities in applied mechanics and applied mathematics such as the fields of solid & fluid constitutive modeling for coupled fields, applications of geophysical & environmental context in judicious numerical-computational implementations. The book aims to merge foundation aspects of continuum mechanics with modern technological applications, notably on reviewing recent advances in the treated subjects in an attractive presentation accessible to a wide readership of engineering and applied sciences.